Language attitudes toward Global Englishes: Is Thai accented English our identity? - Charatwattananich, Monparath; Proces, Jeremy (Universitas Syiah Kuala, 2024)
This study examines language attitudes toward Global Englishes (GE) among employees of multinational companies in Thailands Chonburi and Rayong provinces. Sequential mixed-method research is applied. The survey questionnaires were first distributed and a total of 120 participants responded. The participants were employees in multinational companies and used English as their primary working language. The analysis of questionnaires revealed a prevailing inclination towards native speakerism while acknowledging the importance of GE in the global workplace. Participants demonstrated proficiency in communicating with both native and non-native English speakers. An in-depth interview approach is used with 10 informants for confirming or disconfirming the survey results. However, interviews highlight a complex attitude towards GE, particularly among high-ranking individuals who strongly adhere to standard English ideology. Nonetheless, a significant number of participants recommended introducing GE concepts to Thai students as a valuable step towards familiarizing them with diverse English varieties. This recognition of the need to prepare the next generation for a globalized world is encouraging. The prevalence of native speakerism underscores the urgency of addressing language attitudes and promoting linguistic inclusivity within the global workplace. By fostering on cultural awareness and embracing linguistic diversity, we can create a more inclusive environment that appreciates and values different English accents and expressions. This study highlights the ongoing importance of these efforts in promoting a comprehensive understanding of GE and nurturing a global mindset among individuals and institutions alike.